2020
DOI: 10.1007/s11250-020-02338-y
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the pork value chain in Vietnam: a systematic review

Abstract: In Vietnam, pork is the most commonly consumed type of meat, and the demand is expected to rise even further. Nevertheless, food safety is a major concern, as the country bears a high burden of food-borne diseases, including these caused by pork products. Knowledge of the flows of pigs and pork from producers up to the consumers is important; however, up to now, a comprehensive overview is lacking. We addressed this by conducting a systematic review on the pork value chain (PVC) mapping for the country. Four i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
(21 reference statements)
0
11
0
Order By: Relevance
“…However, the small number of poultry and pig farms sampled might not be entirely representative of the diversity of bla CTX-M -Ec harboured in food animals in Vietnam. The origin of slaughtered animals, currently untraceable due to the lack of record systems and the involvement of multiple stakeholders in the food value chain [28], further hampered our efforts to define an epidemiological network. Another potential study limitation was the high proportion of children/infants among the recruited patients: 114/137 were <5 years old and 41/137 were <1 year old.…”
Section: Discussionmentioning
confidence: 99%
“…However, the small number of poultry and pig farms sampled might not be entirely representative of the diversity of bla CTX-M -Ec harboured in food animals in Vietnam. The origin of slaughtered animals, currently untraceable due to the lack of record systems and the involvement of multiple stakeholders in the food value chain [28], further hampered our efforts to define an epidemiological network. Another potential study limitation was the high proportion of children/infants among the recruited patients: 114/137 were <5 years old and 41/137 were <1 year old.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, notwithstanding the improvement of hygienic standards and living conditions in Vietnam in last decades, our study has shown that T. solium transmission still occurs in communities in Phu Tho Province. The consumption of raw pork and vegetables combined with traditional pig husbandry systems, poor meat inspection procedures [ 28 , 29 ], and the common habit of using night soil on agricultural lands [ 8 ] are likely to perpetuate the transmission of tapeworm infections. Health education campaigns are needed in this area to inform the population on those infection risks.…”
Section: Discussionmentioning
confidence: 99%
“…Meat inspection is only carried out at slaughter points that operate at the district level and/or clusters of large villages [ 63 ]. Vietnam’s pork production for traditional and commercial markets have a poor supply chain; therefore, the weak linkages between actors and poor hygienic practices in these chains create risk [ 66 ]. Most slaughterhouse workers seldom go through food safety training [ 66 ].…”
Section: Ntds Risingmentioning
confidence: 99%
“…Vietnam’s pork production for traditional and commercial markets have a poor supply chain; therefore, the weak linkages between actors and poor hygienic practices in these chains create risk [ 66 ]. Most slaughterhouse workers seldom go through food safety training [ 66 ]. Overall improved sanitation and meat inspection/control are needed to decrease cysticercosis incidence and transmission [ 67 ].…”
Section: Ntds Risingmentioning
confidence: 99%
See 1 more Smart Citation